Hubungan Berat Badan Lahir Rendah (BBLR) dengan Hiperbilirubinemia di RSUP Prof. Dr. R. D. Kandou Manado - Gumogar, Serenity Y. E.; Rompis, Johnny L.; Wilar, Rocky (Medical Scope Journal, 2025)
Abstract: Low birth weight (LBW) is baby whose weight at birth is less than 2,500 grams regardless of gestational age. Meanwhile, hyperbilirubinemia is a condition defined as an increase in serum or plasma bilirubin levels above the normal range of laboratory results caused by bilirubin metabolism disorders characterized by yellowing in infants. This study aimed to determine the relationship between LBW and the incidence of hyperbilirubinemia in neonates at Prof. Dr. R.D. Kandou Hospital Manado. This was an analytical and observational study with a cross-sectional design. Data were obtained from medical records using purposive sampling and then were analyzed using the Pearson chi-square test. The statistical test result showed that there was a significant relationship between LBW and the incidence of hyperbilirubinemia (p<0.001). In conclusion, there is a significant relationship between low birth weight (LBW) and the incidence of hyperbilirubinemia in neonates. Keywords: low birth weight; hyperbilirubinemia Abstrak: Berat badan lahir rendah (BBLR) adalah bayi yang berat badan saat lahir kurang dari 2.500 gram tanpa memandang usia kehamilan. Hiperbilirubinemia adalah peningkatan kadar bilirubin serum atau plasma di atas kisaran hasil normal laboratorium, yang disebabkan gangguan metabolism bilirubin, ditandai dengan kekuningan pada bayi. Penelitian ini bertujuan untuk mengetahui hubungan BBLR dengan kejadian hiperbilirubinemia pada neonatus di RSUP Prof. Dr. R. D. Kandou Manado. Penelitian ini menggunakan metode observasional analitik dengan desain potong lintang. Data diperoleh melalui rekam medis dengan penentuan sampel purposive sampling kemudian dianalisis dengan uji statistik Pearson chi-square yang menunjukkan terdapat hubungan bermakna antara BBLR dengan kejadian hiperbilirubinemia (p<0,001). Simpulan penelitian ini ialah terdapat hubungan bermakna antara berat badan lahir rendah dengan kejadian hiperbilirubinemia pada neonatus. Kata kunci: berat badan lahir rendah; hiperbilirubinemia